2017
DOI: 10.1093/ofid/ofx106
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of High Mortality and Increasing Burden of Sepsis in a Regional Sample of the New Zealand Population

Abstract: BackgroundSepsis is a life-threatening complication of infection. The incidence of sepsis is thought to be on the increase, but estimates making use of administrative data in the United States may be affected by administrative bias.MethodsWe studied the population-based incidence of sepsis in the Waikato region of New Zealand from 2007 to 2012 using International Classification of Diseases, Tenth Revision, Australian Modification, which lacks a specific code for sepsis.ResultsBetween 2007 and 2012, 1643 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…More admissions among M aori were attributable to infection, a criterion in our audit that spans multiple APD diagnostic categories. Despite not reaching statistical significance, this is consistent with a previous analysis of sepsis in the Waikato region, 13 and in combination with the higher rates of admission with APD-defined sepsis for M aori in our study, probably reflects a real finding. M aori are also over-represented in trauma admissions, consolidating previous findings at other NZ centres.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More admissions among M aori were attributable to infection, a criterion in our audit that spans multiple APD diagnostic categories. Despite not reaching statistical significance, this is consistent with a previous analysis of sepsis in the Waikato region, 13 and in combination with the higher rates of admission with APD-defined sepsis for M aori in our study, probably reflects a real finding. M aori are also over-represented in trauma admissions, consolidating previous findings at other NZ centres.…”
Section: Discussionsupporting
confidence: 91%
“…8,9 Previous literature has identified inequity in critical illness admissions for M aori, including trauma, 10,11 stroke 12 and severe infections. 13,14 There is, however, no literature describing M aori health outcomes in a general intensive care unit (ICU) population not specified to a type of presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis was ranked in the top four most costly conditions, costing an aggregate of $20,298,000 million yearly, in US hospitals between all four payer groups (Medicare, Medicaid, private insurers, and uninsured) [4]. This burden on the healthcare system has led to researchers attempting to redefine sepsis and understand its pathophysiologic basis [5,6]. A recent taskforce led by the Society of Critical Care Medicine and the European Society of Intensive Care Medicine convened and redefined sepsis as life threatening organ dysfunction caused by a dysregulated host response to infection [7].…”
Section: Introductionmentioning
confidence: 99%
“…A common perspective among participants highlighted the inequities and disparities in health outcomes between Māori and non‐Māori patients, particularly regarding identification of sepsis. A Waikato study found that Māori patients are three times more likely to develop sepsis and are at increased risk of hospital death 9 . Variation in health outcomes according to ethnicity is not unique to NZ; Indigenous Australians are more likely to die from sepsis at a younger age, 33 and in the USA, African American and Hispanic patients have higher rates of sepsis and are more likely to be admitted to ICU 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant advances in emergency and intensive care medicine, morbidity and mortality remain high; particularly in those who develop shock or have significant pre‐existing medical comorbidities 6–8 . In NZ, the in‐hospital and 1‐year mortality from sepsis is estimated to be 19 and 38%, respectively 9 …”
Section: Introductionmentioning
confidence: 99%